Landau-level width : magnetic-field and temperature dependences - Wang, Lipo. (2012)
We calculate the effect of level broadening on the steady part of the magnetic moment and specific heat by deriving an analytic expression for the free energy of a two-dimensional electron gas in a uniform magnetic field, with an arbitrary Landau-level broadening and at a finite temperature. Measurements of these effects may provide a new way for gaining more information about the magnetic-field and temperature dependences of the Landau-level width. This in turn may lead to information about the density of states. In the particular case of Gaussian broadening, the broadening correction to the steady magnetic moment is as large as the steady magnetic moment itself.